Therapeutic instruments used in therapeutic interventions: is there evidence in nursing care?: a systematic review of the literature - Basto, Marta Lima (2012)
Nursing development depends on clarification of terms currently used, but apparently with different meanings. That is the case of therapeutic interventions and therapeutic instruments. The present article tries to answer the following research question: “Which nursing interventions are considered therapeutic and what are their characteristics?” It was hoped that the meaning of therapeutic instruments would be achieved. A systematic review of the literature on nursing therapeutic interventions was done based on well known data basis through which were achieved 13 articles dated from 1993 to 2006. There is some degree of evidence of the use of therapeutic nursing interventions and general agreement on its meaning. Identified therapeutic instruments used by nurses in therapeutic interventions were: therapeutic letters, bathing and comforting care, humour, music, presence, mindfulness (cognitive therapy), therapeutic touch, information management and emotional management. The concept therapeutic instrument used in nursing needs maturation, justifying a concept clarification study.